Communication Culture In Korean - Yusupova, Gulchekhra Alisherovna (The journal of contemporary issues in business and government, 2021)
This article describes the culture of communication in Korean and the national traditions adopted in Korean society as well as address words. Without communication, it is impossible to imagine the development of a person, his socialization, the formation of an individual as a person, his relationship with society. Communication is also a special need. As the Polish psychologist E. Melibruda said, interpersonal relations are as important to us as air. In infancy and adolescence, communication is embodied as an activity that directly affects leadership, that is, the formation of new psychological characteristics. Communication is a multifaceted process of developing connections between people, arising from the need for cooperation. Communication involves the exchange of information between cooperators. This takes into account the communicative aspect of the relationship. When people enter into a relationship, they turn to language first. Another aspect of communication is the interaction of interlocutors - the exchange of not only words, but also actions in the speech process.